Analisis Manual Material Handling Berdasarkan Prinsip Biomekanika (Studi Kasus CV. Titian Mandiri) - Puthut Supri Adi; Bambang Suhardi; Rahmaniyah Dwi Astuti (Performa: Media Ilmiah Teknik Industri, 2005)
CV. Titian Mandiri is a company that produce bottling water which still use manual lifting method. The advantages of this method are more flexible, effective and low cost. On the other hand, bad manual lifting can generate pain in several operator body segments, such as hand, back, waist and thigh.Leave from those reality, it is needed to do some working method analysis and improvement based on biomechanical principle. NIOSH method used to know lifting safety limit and Chaffin-Anderson equation used to predictable the force that happened on abdominal segment, L5/S1 and operators hand segment. This study shows that RWL value for lifting to pick up car is 8,223 kg and lifting to the box car is 6,208 kg. The LI value for lifting to pick up car is 2,311 and for lifting to box car is 3,060.The improvement of working method was done by rearrange the gallon position and add amount of table. The high of the table is 52 cm and the gallon position would be in front of operator sagital line exactly. This improvement changes RWL value for lifting to pick up become 13,820 kg and 11,475 kg for lifting to the box car. LI value for lifting to the pick up descend become 1,374 and LI value for lifting to the box car become 1,6557.